Fecal microbiota transplantation alleviates female offspring’s ovarian inflammation in arsenic and fluoride co-exposed rats through the PI3K/ Akt /NF-κB pathway - Yidi Li; Dongcai Yue; Yannan Zhao; Penghui Liu; Meng Li; Jinyao Chen; Xiaoting Yan; Linhua Fan; Guohua Song; Xiaolin Tian; Yi Lv; Qian Zhao; et al. (Ecotoxicology and Environmental Safety)
Numerous studies have shown that exposure to arsenic (As) or fluoride(F) can damage the reproductive system, but limited evidence exists regarding the combined toxicity and pathogenesis of As and F co-exposure in female reproduction. Moreover, the role of gut microbiota in mediating such toxicity remains unclear. This study investigated the effects of As and F co-exposure on ovarian development and the potential protective role of fecal microbiota transplantation (FMT). We established an animal model of ovarian injury induced via co-exposure to NaAsO2 and NaF from birth to postnatal day 120(PND120) and introduced FMT from PND60. Co-exposure reduced serum levels of estradiol(E2) and luteinizing hormone (LH), along with morphological alterations in ovarian tissue. Meanwhile, the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/nuclear transcription factor-κB (NF-κB) pathway, a known mediator of inflammation-related ovarian dysfunction, was significantly upregulated. Interestingly, with prolonged exposure, the inflammatory indicators (Akt, IL-1β, IL-6, TNF-α) on PND120 were significantly higher than those on PND60. Notably, FMT alleviated ovarian inflammation, potentially by improving colonic barrier function, thereby indirectly mitigating ovarian damage. Taken together, this study reveals that NaAsO2 and NaF co-exposure induces progressive ovarian inflammation via the PI3K/Akt/NF-κB pathway, and that FMT may offer protective effects. Our findings provide new insights into the environmental risks to female reproductive health.